Ellagitannin HeT obtained from strawberry leaves is oxidized by bacterial membranes and inhibits the respiratory chain. Issue 2 (4th January 2018) - Martos, Gustavo G.; Mamani, Alicia; Filippone, María P.; Abate, Pedro O.; Katz, Néstor E.; Castagnaro, Atilio P.; Díaz Ricci, Juan C.
Abstract : Plant secondary metabolism produces a variety of tannins that have a wide range of biological activities, including activation of plant defenses and antimicrobial, anti‐inflammatory and antitumoral effects. The ellagitannin HeT (1‐ O ‐galloyl‐2, 3;4, 6‐bis‐hexahydroxydiphenoyl‐β‐d ‐glucopyranose) from strawberry leaves elicits a strong plant defense response, and exhibits antimicrobial activity associated to the inhibition of the oxygen consumption, but its mechanism of action is unknown. In this paper we investigate the influence of HeT on bacterial cell membrane integrity and its effect on respiration. A β‐galactosidase unmasking experiment showed that HeT does not disrupt membrane integrity. Raman spectroscopy analysis revealed that HeT strongly interacts with the cell membrane. Spectrochemical analysis indicated that HeT is oxidized in contact with bacterial cell membranes, and functional studies showed that HeT inhibits oxygen consumption, NADH and MTT reduction. These results provide evidence that HeT inhibits the respiratory chain. Abstract : Plants produce a range of tannins, secondary products that have antimicrobial effects. The ellagitannin HeT from strawberry leaves exhibits antibacterial activity on Gram‐positive Clavibacter michiganensis . HeT does not disrupt bacterial membrane integrity, but is oxidized when in contact with the bacterial membrane, causing the irreversible inhibition of the respiratory chain.